Motor vehicle collisions : medical, psychosocial, and legal consequences. - Duckworth, Melanie; Iezzi, Tony.; O'Donohue, William; ScienceDirect eBooks (Amsterdam : Academic Press, 2008)
This book is a comprehensive review of the motor vehicle collision (MVC) experience and includes chapters relevant to the assessment and treatment of multiple consequences of MVC involvement, including medical, psychosocial, and legal difficulties. The book is designed to be accessible to both clinicians and researchers interested in the study of MVCs and in the management of MVC-related problems. The aim of this book is to capture the MVC experience from a multidisciplinary perspective, This book will serve as a necessary reference for physicians, rehabilitation specialists, allied medical professionals, psychologists, and lawyers. * Presents the complete chronology of an MVC from immediate aftermath to chronic disability * Details evidence-based assessment and treatment practices across disciplines * Addresses cultural factors that influence assessment and treatment of MVC sufferers.
Section IThe Scope and Significance of Motor Vehicle Collisions -- 1. Introduction to Motor Vehicle Collisions: Medical, Psychosocial, and Legal Consequences -- Melanie P. Duckworth, Tony Iezzi, William T. ODonohue -- 2. The Prevalence and Impact of Motor Vehicle Collisions -- Ted Miller -- 3. Predictors of Motor Vehicle Collisions -- Graham Hole -- Section IIManaging the Immediate Motor Vehicle Collision Aftermath -- 4. Assessment of Acute Pain, Physical Injury, and Disability Consequent to Motor Vehicle Collisions -- Murray Girotti and Neil Parry -- 5. Treatment of Acute Pain, Physical Injury, and Disability Consequent to Motor Vehicle Collisions -- David B. Hoyt -- 6. Emergency Room Trauma: The Immediate Aftermath of Motor Vehicle Collisions -- Therese S. Richmond -- 7. Acute Stress Disorder Consequent to Motor Vehicle Collisions -- Richard A. Bryant -- Section IIIManaging the Consequences of Motor Vehicle Collisions in the Primary Care Setting -- 8. Normalizing Experiences of Acute Pain and Injury-Related Impairment -- Keith Sequeira -- 9. Normalizing Emotional Distress -- Michael Lewandowski -- 10. Managing Primary Care Costs: Medical and Psychological Cost-Offset -- William T. ODonohue -- Section IVChronic Physical and Psychological Consequences of Motor Vehicle Collisions -- 11. Assessment of Patients with Whiplash Associated Disorders -- Dennis Turk and James Robinson -- 12. Treatment of Chronic Pain Consequent to Motor Vehicle Collisions -- Robert J. Gatchel -- 13. Neuropathology and Severity of Traumatic Brain Injury Consequent to a Motor Vehicle Collisions -- H. Julia Hannay -- 14. Cognitive Impairment Consequent to Motor Vehicle Collisions -- Grant Iverson -- 15. Psychological Conditions Associated with Motor Vehicle Collisions -- Meaghan ODonnell and Mark Creamer -- 16. Assessment of PTSD Consequent to Motor Vehicle Collisions -- Melanie P. Duckworth -- 17. Treatment of PTSD Consequent to Motor Vehicle Collisions -- Edward J. Hickling and Eric Kuhn -- 18. Driving Phobia Associated with Motor Vehicle Collisions -- Joanne Taylor -- Section VMedical-Legal Issues Associated with Motor Vehicle Collisions -- 19. Medical-Legal Issues: A Legal Perspective -- Stephen Schenke -- 20. Medical-Legal Issues: A Medical Perspective -- Nathan D. Zasler and Michael F. Martelli -- 21. Medical-Legal Issues: A Psychological Perspective -- Tony Iezzi -- 22. Medical-Legal. Issues: A Patients Perspective -- Melanie P. Duckworth and Tony Iezzi -- Section VISummary, Conclusions, and Future Directions -- 23. Current Status and Future Directions in the Study of Motor Vehicle Collisions and the Associated Medical, Psychosocial, and Legal Consequences -- Tony Iezzi, Melanie P. Duckworth, and William T. ODonohue.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Traffic accidents; Traffic accidents; Electronic books